Regioselective and Catalyst-Free Epoxidation of (E)-3-[3-(2-Hydroxyaryl)-3-oxoprop-1-en-1-yl]chromones - Ameraoui, Rachid; Hammadi, Mohamed; Talhi, Oualid; Hassaine, Ridha; Bouchama, Abdelghani; Abdeldjebar, Hasnia; Belmiloud, Yamina; Brahimi, Meziane; Paz, Filipe A. Almeida; Bachari, Khaldoun; Silva, Artur M. S. (Synlett, 2018)
The uncatalyzed reaction of hydrogen peroxide with (E)-3-[3-(2-hydroxyaryl)-3-oxoprop-1-en-1-yl]chromones resulted in a regioselective epoxidation of the chromone intracyclic C(2)=C(3) double bond to afford unique isomeric (E)-7a-[3-(2-hydroxyphenyl)-3-oxoprop-1-en-1-yl]-1aH-oxireno[2,3-b]chromen-7(7aH)-ones in high yields. 2D NMR and single-crystal X-ray diffraction were used to elucidate the structures of the chromanone epoxides. Density functional theoretical studies demonstrated a high electrophilicity of the starting chromones.
Keywords: chromones; epoxidation; regioselectivity; NMR; X-ray diffraction; density functional theory